Analysis of Islamic Law and Law No. 56 PRP 1960 on the Practice of Pawning Paddy Fields in the Village of Malang - Hanik Musyarofah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2021)
This is field research entitled